Load balancing on stateful clustered Web servers - Teodoro, G.; Tavares, T.; Coutinho, B.; Meira, W.; Guedes, D. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2003: Anais do XV Symposium on Computer Architecture and High Performance Computing, 2003)
One of the main challenges to the wide use of the Internet is the scalability of the servers, that is, their ability to handle the increasing demand. Scalability in stateful servers, which comprise e-commerce and other transaction-oriented servers, is even more difficult, since it is necessary to keep transaction data across requests from the same user. One common strategy for achieving scalability is to employ clustered servers, where the load is distributed among the various servers. However, as a consequence of the workload characteristics and the need of maintaining data coherent among the servers that compose the cluster, load imbalance arise among servers, reducing the efficiency of the server as a whole. We propose and evaluate a strategy for load balancing in stateful clustered servers. Our strategy is based on control theory and allowed significant gains over configurations that do not employ the load balancing strategy, reducing the response time in up to 50% and increasing the throughput in up to 16%.